Modelling and optimization of production of coffee-like powder and brew from palm date seeds by roasting and grinding - Ahmed, Ibrahim Mohamed Fikry Mohamed (2019)
A significant quantity of date seeds is being generated annually from palm date industry. This by-product is usually discarded or used as an animal fodder. However, palm dates seeds can be a potential source of nutritious elements and antioxidants which could be used for human consumption in a powder form and decaffeinated coffee-like brew.